2020
DOI: 10.3390/met10081072
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Enabled Prediction of Stacking Fault Energies in Concentrated Alloys

Abstract: Recent works have revealed a unique combination of high strength and high ductility in certain compositions of high-entropy alloys (HEAs), which is attributed to the low stacking fault energy (SFE). While atomistic calculations have been successful in predicting the SFE of pure metals, large variations up to 200 mJ/m2 have been observed in HEAs. One of the leading causes of such variations is the limited number of atoms that can be modeled in atomistic calculations; as a result, due to random distribution of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 48 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…(The SFE estimation using the microstrain method is attached in supplementary information I, section S5). The table shows that the predicted SFE is similar to the reported SFE values calculated from experimentation and atomistic calculations [5,29,30,[55][56][57][58]. The error percentage is below 25% showing a good resemblance with the reported value and acceptable for the SFE prediction.…”
Section: Tuning Sfe Using Mlpnn Modelsupporting
confidence: 74%
See 1 more Smart Citation
“…(The SFE estimation using the microstrain method is attached in supplementary information I, section S5). The table shows that the predicted SFE is similar to the reported SFE values calculated from experimentation and atomistic calculations [5,29,30,[55][56][57][58]. The error percentage is below 25% showing a good resemblance with the reported value and acceptable for the SFE prediction.…”
Section: Tuning Sfe Using Mlpnn Modelsupporting
confidence: 74%
“…A few approaches have strived to overcome this limitation using data obtained from atomistic calculations. Arora and Aidhy [29] reportedly built a framework for the prediction of SFE for multi-elemental alloys, trusting on the inputs of binary alloys i.e. Ni-Fe, Fe-Cr, and Cr-Ni data obtained via atomistic calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sharma et al (2020) used ML based framework to predict substitutional defect formation energies in ABO 3 perovskites. Other materials properties such as vibrational entropy (Manzoor and Aidhy, 2020) and stacking fault energies (Arora and Aidhy, 2020) have also been recently predicted using a combination of ML and atomistic calculations. Thus, application of ML models in materials science is rapidly becoming mainstream that is being used not only to bypass the computational expense but also to predict new properties.…”
Section: Introductionmentioning
confidence: 99%
“…Vilalta et al [39] examined the relationship between yield stress and the γ SFE landscape in high entropy alloys by means of a ML approach. Arora and Aidhy [40] indicated that γ SFE in concentrated multi-elemental alloys can be predicted using a ML based framework. However, the ML based study of γ SFE affected by dilute alloying elements is not available in the literature.…”
Section: Introductionmentioning
confidence: 99%